2006
DOI: 10.1091/mbc.e06-03-0230
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Trafficking of MDR1/P-Glycoprotein to Apical Canalicular Plasma Membranes in HepG2 Cells Requires PKA-RIIα Anchoring and Glucosylceramide

Abstract: In hepatocytes, cAMP/PKA activity stimulates the exocytic insertion of apical proteins and lipids and the biogenesis of bile canalicular plasma membranes. Here, we show that the displacement of PKA-RIIalpha from the Golgi apparatus severely delays the trafficking of the bile canalicular protein MDR1 (P-glycoprotein), but not that of MRP2 (cMOAT), DPP IV and 5'NT, to newly formed apical surfaces. In addition, the direct trafficking of de novo synthesized glycosphingolipid analogues from the Golgi apparatus to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 58 publications
2
64
0
1
Order By: Relevance
“…Bile canalicular lumens were first identified with phase contrast and scored as NBD positive or negative with epifluorescence. Figure 6, A-D, shows that the lipid analogue reached the apical surface domain in untreated or OSM-treated cells expressing the AKAP-IS peptide, similarly as previously shown in control HepG2 cells Hoekstra, 1999, 2000;van der Wouden et al, 2002) and consistent with previous results (Wojtal et al, 2006). Basolaterally derived NBD-sphingomyelin reached 74 and 89% of the bile canalicular lumens after a chase of 15 and 30 min, respectively, in parental cells.…”
Section: Expression Of the Pka-displacing Akap-is Peptide Does Not Insupporting
confidence: 89%
See 3 more Smart Citations
“…Bile canalicular lumens were first identified with phase contrast and scored as NBD positive or negative with epifluorescence. Figure 6, A-D, shows that the lipid analogue reached the apical surface domain in untreated or OSM-treated cells expressing the AKAP-IS peptide, similarly as previously shown in control HepG2 cells Hoekstra, 1999, 2000;van der Wouden et al, 2002) and consistent with previous results (Wojtal et al, 2006). Basolaterally derived NBD-sphingomyelin reached 74 and 89% of the bile canalicular lumens after a chase of 15 and 30 min, respectively, in parental cells.…”
Section: Expression Of the Pka-displacing Akap-is Peptide Does Not Insupporting
confidence: 89%
“…The expression level of PKA-RII␣ in cells expressing the peptide was not changed compared with parental HepG2 cells (cf. Wojtal et al, 2006). Importantly, in contrast to parental HepG2 cells or HepG2 cells expressing the scrambled peptide, treatment of cells expressing the AKAP-IS peptide with OSM at 37°C for 4 h did not result in an increase in the percentage of centrosomes that contained PKA-RII␣ ( Figure 3A), confirming that OSM stimulated the association of PKA-RII␣ with centrosomes in parental HepG2 cells by promoting its AKAP-mediated anchoring.…”
Section: Inhibition Of Pka-rii␣ Anchoring At Centrosomes Interferes Wmentioning
confidence: 68%
See 2 more Smart Citations
“…4 Several studies have suggested the ability of PKC and PKA to increase the functionality of MDR1 or its membrane integration. 29,30 Other studies showed that the preferential localization of MDR1 in the lipid rafts and caveolae, characterized as detergent resistant membranes (DRM), is required for its functionality. 31,32 Indeed, cholesterol depletion that disrupts lipid rafts, abolishes membrane MDR1 localization and is associated with reduced efflux capacities.…”
Section: Introductionmentioning
confidence: 99%